Isolasi dan Karakterisasi Senyawa Triterpenoid dari Ekstrak Etil Asetat Daun Salam (Syzygium polyanthum (Wight) Walp.) serta Uji Sitotoksik Menggunakan Metode BSLT (Brine Shrimp Lethality Test) - Ferdinal, Norman; Muhamad Fadli; Rizki Septiardi; Adlis Santoni (Jurnal Kimia Unand, 2023)
The bay plant (Syzygium polyanthum (Wight) Walp.) is a member of the myrtaceae family. The most widely used part of the bay plant is the bay leaf. The leaves of this plant are often used as traditional medicine to treat gout, diarrhea, diabetes, and high blood pressure. This study aims to isolate and determine the characteristics of triterpenoid compounds from ethyl acetate extract of bay leaves. Isolation was carried out by column chromatography method with SGP (Step Gradient Polarity) elution system, then the isolated compound was purified by recrystallization method and obtained in the form of white crystals weighing 0.0188 g. TLC results showed a single purple spot after being treated with Liebermann Buschard reagent with a melting point range of 137-139 oC. The results of the UV spectrum data showed no conjugated double bonds and the results of the FTIR spectrum data showed the presence of hydroxyl groups, C-O alcohols, C-H alkanes, C=C alkenes, geminal dimethyl which are characteristic of triterpenoid compounds. Cytotoxic activity testing was carried out using the Brine Shrimp Lethality Test (BSLT) method.  Ethyl acetate extract and methanol extract had strong cytotoxic activity with LC50 values 316.23 mg/L and 234.42 mg/L respectively, while the hexane extract was weak with an LC50 value of 1148.15 mg/L.